2005
DOI: 10.1021/jm049306x
|View full text |Cite
|
Sign up to set email alerts
|

Partition-Variant Desferrithiocin Analogues:  Organ Targeting and Increased Iron Clearance

Abstract: Altering the lipophilicity (log P(app)) of desferrithiocin analogues can change the organ distribution of the chelators and lead to enhanced iron clearance. For example, alkylation of (S)-2-(2,4-dihydroxyphenyl)-4,5-dihydro-4-methyl-4-thiazolecarboxylic acid [(S)-4'-(HO)-DADFT] and its analogues to more lipophilic compounds, such as (S)-4,5-dihydro-2-(2-hydroxy-4-methoxyphenyl)-4-methyl-4-thiazolecarboxylic acid [(S)-4'-(CH3O)-DADFT], provides ligands that achieved between a 3- and 8-fold increase in chelator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 68 publications
1
45
0
Order By: Relevance
“…The previous studies with ligands [1,2] and [7,8] clearly indicated that the more lipophilic chelators had greater ICE values. 43 In the current study with [3,4] and [9,10], again the more lipophilic ligand was the more efficient (4 > 3, p < 0.001 and 10 > 9, p < 0.003). While the polyether (6) follows the expected trend, the dimethoxy systems 5 and 11 were not well behaved within the DADFT and DADMDFT families; their ICEs were higher than anticipated.…”
Section: Chelator-induced Iron Clearance In Non Iron-overloaded Rodentsmentioning
confidence: 54%
“…The previous studies with ligands [1,2] and [7,8] clearly indicated that the more lipophilic chelators had greater ICE values. 43 In the current study with [3,4] and [9,10], again the more lipophilic ligand was the more efficient (4 > 3, p < 0.001 and 10 > 9, p < 0.003). While the polyether (6) follows the expected trend, the dimethoxy systems 5 and 11 were not well behaved within the DADFT and DADMDFT families; their ICEs were higher than anticipated.…”
Section: Chelator-induced Iron Clearance In Non Iron-overloaded Rodentsmentioning
confidence: 54%
“…Catechols C [R = Cl, Br, I, Me, CF 3 CH(OH)], isolated during this study, showed identical physical and spectral characteristics to those reported. [2,3,7,40] (À)-cis-(1S,2R)-3-Methyl-3-cyclohexene-1,2-diol D (R = Me) Biotransformation Using P. putida UV4 to Yield cisDihydrodiols B Biotransformation procedures employed for arene substrates A (including 1,5-D 2 -and D 8 -toluene) with whole cells of P. putida UV4, a proprietary constitutive mutant strain derived from the wild type strain P. putida NCIB 11767, were identical to those reported earlier for the production of cis-dihydrodiols B. [3,12,35,36] Biotransformation Using E. coli nar B to Yield Catechols C E. coli nar B was grown at 37 8C in Luria broth (LB) medium.…”
Section: Methodsmentioning
confidence: 99%
“…Oxazolidine 13 was afforded by the reaction of a L-threonine derivative with 12, [8][9][10] which was derived from 10. Carboxylic acid 14 11) was afforded in 80% yield by the hydrogenolysis of 13.…”
Section: )mentioning
confidence: 99%